Specific Flavonoids and Their Biosynthetic Pathway in Scutellaria baicalensis - Pei, Tianlin; Yan, Mengxiao; Huang, Yanbo; Wei, Yukun; Martin, Cathie; Zhao, Qing (Frontiers in Plant Science, 2022)
Scutellaria baicalensis, is one of the most traditional medicinal plants in the Lamiaceae family, and has been widely used to treat liver and lung complaints and as a complementary cancer treatment in traditional Chinese medicine. The preparation from its roots, called “Huang Qin”, is rich in specialized flavones such as baicalein, wogonin and their glycosides which lack a 4′-hydroxyl group on the B ring (4′-deoxyflavones), with anti-tumor, antioxidant and antiviral activities. Baicalein has recently been reported to inhibit the replication of the COVID-19 virus. These 4′-deoxyflavones are found only in the order Lamiales and were discovered in the genus Scutellaria, suggesting that a new metabolic pathway synthesizing 4′-deoxyflavones evolved recently in this genus. In this review, we focus on the class of 4′-deoxyflavones in S. baicalensis and their pharmacological properties. We also describe the apparent evolutionary route taken by the genes encoding enzymes involved in the novel, root-specific, biosynthetic pathway for baicalein and wogonin, which provides insights into the evolution of specific flavone biosynthetic pathways in the mint family.